The Grail : from Celtic myth to Christian symbol - Loomis, Roger Sherman, 1887-1966 (Mythos (Princeton, N.J.), 1991)
"The medieval legend of the Grail, a tale about the search for supreme mystical experience, has never ceased to intrigue writers and scholars by its wildly variegated forms: the settings have ranged from Britain to the Punjab to the Temple of Zeus at Dodona; the Grail itself has been described as the chalice used by Christ at the Last Supper, a stone with miraculous youth-preserving virtues, or a vessel containing a man's head swimming in blood. In his classic exploration of the major versions, Roger Sherman Loomis shows how the Grail, once a Celtic vessel of plenty, evolved into the Christian Grail with miraculous powers. Loomis bases his argument on historical examples involving the major motifs and characters in the legends, beginning with the Arthurian legend recounted in the 1180 French poem by Chrétien de Troyes. Loomis's book builds suspense as he proceeds from one puzzle to the next in revealing the meaning behind the legends"--